Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Service Learning (SL) Pada Materi Pencemaran Lingkungan Kelas VII SMP IT Qurrata A’yun Sungayang - Elsaniati Tanjung; Diyyan Marneli; Rina Delfita; Najmiatul Fajar (Edusainstika: Jurnal Pembelajaran MIPA, 2021)
The purpose of this research is to produce a product in the form of service learning (SL)- based LKPD on environmental pollution material for class VII SMP IT Qurrata A'yun Sungayang that is valid and practical. The type of research applied through this activity is research and development using a 4-D model consisting of define, design, develop and disseminate stages. However, what is developed is only up to the develop stage. The results obtained are service learning-based LKPD (SL) has validity with an average result of 90.12% with a very valid category, and the average practicality of teachers obtained is 93.34% with a very practical category and an average practicality The number of students obtained is 83.72% with a very practical category, so that service learning-based worksheets can already be used.